A variable-stiffness and healable pneumatic actuator. Issue 3 (21st December 2022) - Wang, Hong-Qin; Huang, Zi-Yang; Yue, De-Wei; Wang, Fang-Zhou; Li, Cheng-Hui
Abstract : A pneumatic actuator based on variable-stiffness and self-healing polymers shows high load capacity at room temperature but can be actuated pneumatically upon heating. And it can be thermally healed after damaging, thus can prolong its service time. Abstract : Pneumatic-powered actuators are receiving increasing attention due to their widespread applications. However, their inherent low stiffness makes them incompetent in tasks requiring high load capacity or high force output. On the other hand, soft pneumatic actuators are susceptible to damage caused by over-pressuring or punctures by sharp objects. In this work, we designed and synthesized a coordination adaptable network (PETMP-AIM-Cu ) with high mechanical rigidity (Young's modulus of 1.9 GPa and elongation <2% before fracturing) as well as excellent variable stiffness property (soft-rigid switching ability σ as high as 3 268 000 when Δ T = 90 °C). Combining PETMP-AIM-Cu with a self-healing elastomer based on dynamic disulfide bonds (LP-PDMS ), we fabricated a new pneumatic actuator which shows high load capacity at room temperature, but can also easily deform upon heating and thus can be actuated pneumatically. Benefiting from the excellent self-healing ability of PETMP-AIM-Cu and LP-PDMS, the entire pneumatic actuator can still be actuated after being cut and healed. Such a variable-stiffness and healable pneumatic actuator would be useful for complex environmental applications.